Rings of the right (left) almost stable range $1 - Bovdi, V.; Zabavsky, B. (Karpats'kì matematinì publìkacìï, 2025)
We introduce a concept of rings of right (left) almost stable range $1$ and we construct a theory of a canonical diagonal reduction of matrices over such rings. A description of new classes of noncommutative elementary divisor rings is done as well. In particular, for Bézout $D$-domain we introduced the notions of $D$-adequate element and $D$-adequate ring. We proved that every $D$-adequate Bézout domain has almost stable range $1$. For Hermite $D$-ring we proved the necessary and sufficient conditions to be an elementary divisor ring. A ring $R$ is called an $L$-ring if the condition $RaR = R$ for some $a\in R$ implies that $a$ is a unit of $R$. We proved that every $L$-ring of almost stable range $1$ is a ring of right almost stable range $1$. У роботі вводиться поняття кілець правого (лівого) майже стабільного рангу $1$ та будується теорія канонічного діагонального зведення матриць над такими кільцями. Також подано опис нових класів некомутативних кілець елементарних дільників. Зокрема, для $D$-області Безу ми ввели поняття $D$-адекватного елемента та $D$-адекватного кільця. Ми довели, що кожна $D$-адекватна область Безу має майже стабільний ранг $1$. Для ермітового $D$-кільця ми встановили необхідні й достатні умови, за яких воно є кільцем з елементарними дільниками. Кільце $R$ називають $L$-кільцем, якщо з умови $RaR = R$ для деякого $a \in R$ випливає, що $a$ є одиничним елементом у $R$. Ми довели, що кожне $L$-кільце майже стабільного рангу $1$ є кільцем із правим майже стабільним рангом $1$.